OARSI–OMERACT initiative: defining thresholds for symptomatic severity and structural changes in disease modifying osteoarthritis drug (DMOAD) clinical trials - Manno, R.L. (Osteoarthritis Cartilage, 2011)
OBJECTIVE: Total joint replacement has been proposed as an endpoint in disease modifying osteoarthritis drug (DMOAD) randomized clinical trials (RCTs); however, disparities have generated concerns regarding this outcome. A combined Osteoarthritis Research Society International (OARSI)/Outcome Measures in Rheumatology (OMERACT) initiative was launched in 2004 to develop a composite index [‘virtual total joint replacement’ (VJR)] as a surrogate outcome for osteoarthritis (OA) progression in DMOAD RCTs. Our objective was to evaluate the prevalence of patients fulfilling different thresholds of sustained pain, reduced function, and X-ray change in existing DMOAD RCTs. DESIGN: Post hoc analysis of summary data from the placebo arm of eight DMOAD RCTs. RESULTS: Eight OA RCTs representing 1379 patients were included. Pain was assessed by WOMAC and/or VAS and function by WOMAC and/or Lequesne. Among six knee and two hip studies, 248 (22%) and 132 (51%) patients respectively had X-ray progression [decrease joint space width (JSW) ≥0.5 mm]. The prevalence of patients fulfilling clinical and radiographic criteria was highest (n = 163, 12%) in the least stringent scenario (pain + function ≥80 at ≥2 visits); with few patients (n = 129, 2%) in the most stringent scenario (pain + function ≥80 at ≥4 visits). Using these prevalence data, a sample size of 352–2144 per group would be needed to demonstrate a 50% difference between groups. CONCLUSIONS: The prevalence of patients with sustained symptomatic OA of at least a moderate degree with X-ray progression is low. Even using lenient criteria to define VJR, large patient numbers would be required to detect differences between groups in DMOAD RCTs. Investigation of the optimal cutoff threshold and combination of symptoms and radiographic change should be pursued.